2021
DOI: 10.3390/horticulturae7110418
|View full text |Cite
|
Sign up to set email alerts
|

Acidified Biochar Confers Improvement in Quality and Yield Attributes of Sufaid Chaunsa Mango in Saline Soil

Abstract: Mango fruit quality plays a significant role in fruit storage. It also directly affects the economic value of fruit in the national and international markets. However, deterioration of soil health due to low organic matter is a major hurdle for mango growers. Scientists suggest incorporation of organic matter. However, high temperature and low precipitation lead to oxidation of organic residues in soil. On the other hand, biochar is gaining the attention of growers due to its resistance against decomposition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…This hormone likely stimulates gene expression in chlorophyll biosynthesis and maintenance. Biochar has a high surface area and porous structure that can serve as a substrate for beneficial microorganisms [62][63][64][65]. These microorganisms can contribute to improved nutrient availability, root health, and overall plant performance, including chlorophyll synthesis [66].…”
Section: Discussionmentioning
confidence: 99%
“…This hormone likely stimulates gene expression in chlorophyll biosynthesis and maintenance. Biochar has a high surface area and porous structure that can serve as a substrate for beneficial microorganisms [62][63][64][65]. These microorganisms can contribute to improved nutrient availability, root health, and overall plant performance, including chlorophyll synthesis [66].…”
Section: Discussionmentioning
confidence: 99%
“…The fruit content from sugars was increased by the addition of biochar to the soil as a result of improving the nutrients and water absorption (Ali et al 2017). Iqbal et al (2013) reported that the addition of biochar at 20 and 40 mg/ha to the soil of mango cv. "Sufaid Chaunsa" significantly enhanced fruit retention, fruit weight, and consequently the fruit yield per plant compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…Commercial mango varieties have largely been grown under varying planting geometries and were maintained by using clonal propagation by grafting of a specific variety or mutated branches [12]. Mango trees are heteroecious and cross-breeding has become dominant with high world popularity.…”
Section: Introductionmentioning
confidence: 99%